Workshop Learning Tools for STEAM Classes to Enhance Learning Process - Prasetyo, Ilham; Alfakihuddin, Muhammad Lukman Baihaqi; Lestari, Tika Endah; Setiawan, Iwan; Tridanisa, Nyayu Rohaya; Wandy, Wandy (Journal of Community Services: Sustainability and Empowerment, 2023)
Online learning tools are in demand these days since the COVID-19 pandemic, which forces everyone, except for some jobs, to work from home. In this community service event, we use three online tools: Nearpod, PhET, and Desmos. Nearpod is a tool learning which combines learning from videos and simulations, the interactivity of a quiz, and a reward-based learning system. PhET is a collection of lots of STEAM simulations, including some topics in Chemistry and Physics. Desmos is an extension of an online graphing calculator, which also has a quiz feature. We introduce these tools to students in East Jakarta's SMP Negeri 174 Jakarta, which is a public junior high school. As a result, the students are now familiar with online tools that can enhance their experience in learning STEAM topics.